Factors affecting the internet banking adoption - Chang, Yung-Chi; Enkhjargal, Uguumur; Huang, Chen-I; Lin, Wen-Ling; Ho, Chi-Ming (Penerbit Universiti Kebangsaan Malaysia, 2020)
Internet banking is a beneficial service; it is less costly, offers the flexibility of time and space, and have excellent customer service. The commercial banks of Mongolia are offering internet banking to its customers to capitalize on its advantages. However, these services remain underutilized by their customers. The factors affecting the use of internet banking in Mongolia remain unknown. This study has integrated the E-service-quality model with the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) to investigate the factors affecting the use of internet banking services offered by the commercial banks in Mongolia. The data was collected through the survey method. Structured Equation Modeling (SEM) was used for the analysis. The results indicate that the E-service quality model is effective and robust. The hypotheses were supported by the data. Attitude, subjective norm, perceived behavioral control, perceived usefulness, and E-service quality were found to be the factors that affect customer’s intentions to use internet banking in Mongolia. In the end, the future recommendations, limitations, and implications of the research are discussed.